Bergey's Manual of Systematics of Archaea and Bacteria 2022
DOI: 10.1002/9781118960608.gbm01517
|View full text |Cite
|
Sign up to set email alerts
|

Crocosphaera

Abstract: Cro.co.sphae'ra. Gr. xxxxx n krokos , the crocus, orange‐colored; Gr. fem. n. sphaera , a ball or sphere; N.L. fem. n. Crococsphaera , an orange ball or sphere, M.L. fem. n., Crocosphaera , an orange ball due to autofluorescence of high urobilin phycoerythrin. Cyanobacteria / Subsection I / Incertae Sedis / Crocosphaera Coccoid, pigmented nonmotile cyanobacterial cells fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The unicellular cyanobacteria Crocosphaera spp. [104] appears to be highly favored for this type of endosymbiotic interaction. In fact, permanent endosymbionts that are closely related to the Crocosphaera genus, particularly Crocosphaera subtropica, are found in various microalgae including the diatoms Epithemia spp.…”
Section: Microalgae Interaction With Photosynthetic Diazotrophic Bact...mentioning
confidence: 96%
“…The unicellular cyanobacteria Crocosphaera spp. [104] appears to be highly favored for this type of endosymbiotic interaction. In fact, permanent endosymbionts that are closely related to the Crocosphaera genus, particularly Crocosphaera subtropica, are found in various microalgae including the diatoms Epithemia spp.…”
Section: Microalgae Interaction With Photosynthetic Diazotrophic Bact...mentioning
confidence: 96%
“…Trichodesmium spp. are a group of filamentous, cyanobacteria that do not form specialized N 2 ‐fixing heterocyst cells (Zehr et al 2023). Trichodesmium species vary greatly in size (6–16 μ m in width and 4–23 μ m long across very diverse species; Hynes et al 2012), and other characteristics (Webb et al 2009, Zehr et al 2023; Hynes et al 2012), but only a few species are typically abundant and found in wide areas of the ocean.…”
Section: The Problem With Defined Size Classes For Key Diazotrophsmentioning
confidence: 99%
“…are a group of filamentous, cyanobacteria that do not form specialized N 2 ‐fixing heterocyst cells (Zehr et al 2023). Trichodesmium species vary greatly in size (6–16 μ m in width and 4–23 μ m long across very diverse species; Hynes et al 2012), and other characteristics (Webb et al 2009, Zehr et al 2023; Hynes et al 2012), but only a few species are typically abundant and found in wide areas of the ocean. Filamentous heterocyst‐forming N 2 ‐fixing cyanobacteria are associated with a number of genera of diatoms that also range in size and physical location of the symbiont, but also the number of filaments per diatom, the number of heterocysts per filament, and the degree of aggregation or chain formation (Caputo et al 2019).…”
Section: The Problem With Defined Size Classes For Key Diazotrophsmentioning
confidence: 99%
See 2 more Smart Citations